Conceptual review on Ayurvedic methodology of Svedan Karma - Bhanudas Kaluram Chatse; Tarkeshwar Sukhadeo Wankhade; Minal Bapurao Sardar (Ayurline: International Journal of Research in Indian Medicine, 2026)
This review focuses on the ancient Ayurvedic therapeutic procedure known as Swedan karma, or sudation therapy, as outlined in classical texts like the Charak Samhita. Swedana, the therapeutic application of heat or steam to induce sweating, is essential in Ayurvedic pretreatment (Pūrvakarma) and specific curative protocols. The methodology involves diverse techniques (Svedana types) and consideration of benefits (Svedana *ke guṇa), potential complications, and specific contraindications (upayogiyo), as discussed primarily in the fourteenth chapter of the classical text. The application of Swedana is aimed at balancing the bodily humors (doṣas) and treating conditions arising from their vitiation, such as pain or urinary issues.